2023
DOI: 10.3390/s23177513
|View full text |Cite
|
Sign up to set email alerts
|

Driving Force Analysis of Natural Wetland in Northeast Plain Based on SSA-XGBoost Model

Hanlin Liu,
Nan Lin,
Honghong Zhang
et al.

Abstract: Globally, natural wetlands have suffered severe ecological degradation (vegetation, soil, and biotic community) due to multiple factors. Understanding the spatiotemporal dynamics and driving forces of natural wetlands is the key to natural wetlands’ protection and regional restoration. In this study, we first investigated the spatiotemporal evolutionary trends and shifting characteristics of natural wetlands in the Northeast Plain of China from 1990 to 2020. A dataset of driving-force evaluation indicators was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Previous studies have indicated that both natural environmental factors and human activities exert varying degrees of influence on wetlands [54,55], suggesting that both likely drive changes in SMWs, which are also integral parts of wetland ecosystem. Combined with their ecological functions and characteristics, we speculated that these factors may also affect SMWs in the Yellow River Basin.…”
Section: Analysis Of Driving Factors Behind Smws Changes Factors Sele...mentioning
confidence: 99%
“…Previous studies have indicated that both natural environmental factors and human activities exert varying degrees of influence on wetlands [54,55], suggesting that both likely drive changes in SMWs, which are also integral parts of wetland ecosystem. Combined with their ecological functions and characteristics, we speculated that these factors may also affect SMWs in the Yellow River Basin.…”
Section: Analysis Of Driving Factors Behind Smws Changes Factors Sele...mentioning
confidence: 99%